Pengaruh perbandingan konsentrasi Lactobacillus plantarum dan gula terhadap karakteristik cuka kulit lemon (Citrus limon) - Gina Firgianti; Yopi Setiawan; Fatyma Azahari (University of Insan Cendekia Mandiri, 2025)
Lemon peel has various benefits and can be processed into higher-value products such as vinegar. Generally, vinegar is an acidic compound composed of acetic acid produced through a two-stage fermentation process. However, in this study, an innovation was introduced to convert acetic acid into lactic acid using Lactobacillus plantarum as the fermenting agent and sugar as the nutrient source. The aim of this study was to determine the effect of varying concentrations of L. plantarum and sugar on the chemical, physical, microbiological, and organoleptic characteristics of lemon peel vinegar. This study employed a Randomized Complete Block Design (RCBD) consisting of two factors: L. plantarum concentration (5%, 10%, 15%) and sugar concentration (15%, 10%, 5%). The results showed that the concentration ratio of L. plantarum and sugar significantly affected several characteristics of the lemon peel vinegar product. The best treatment was found in treatment A3, which used 15% L. plantarum and 5% sugar, with the following characteristics: moisture content of 93.43%, vitamin C content of 41.61 mg/100g, total titratable acidity (TTA) of 0.97%, pH of 2.76, viscosity of 3.72 cP, total plate count (TPC) of 13.75×10⁷ CFU/ml, and organoleptic test scores of 2.66 for color preference, 2.74 for aroma, 2.53 for taste, and 2.68 for texture.